Ayurvedic Management of Yakritodara (Fatty Liver Grade Ll) Associated with Garbhashayagata Granthi (Uterine Fibroid) and Ashma Sharkara (Renal Concretions): A Case Report - Ansari, Sheeba; Yadav, Sujata (International Research Journal of Ayurveda & Yoga, 2025)
Yakritodara (NAFLD) is a major cause of liver-related morbidity in both developed and developing countries. It is frequently associated with the presence of insulin resistance. There is increasing evidence that NAFLD can progress to cirrhosis and liver failure. There is no established treatment for NAFLD. Treatment usually is directed toward optimizing body weight. In Ayurveda, Rakta-Kapha Dushti giving rise to Yakritodara (enlargement of the liver) Garbhashayagatagranthi, mentioned in Ayurveda with vitiated vata affecting mamsa (muscle tissue), rakta (blood) and medas (fat) mixed with kapha. Mutrashmari is the stone formed in urinary tract (kidney, ureter, bladder, and urethra). A 45-year-old female presented to the outpatient department with symptoms of irregular menstruation, body ache, and acidity. On investigation, an ultrasound revealed the presence of a uterine fibroid, Grade Il fatty liver, and renal concretions. The patient underwent Shaman Chikitsa (palliative therapy) according to Ayurvedic principles for a period of 5 months. A follow-up ultrasound showed a complete resolution of the uterine fibroid, along with a reduction in both fatty liver and renal concretions.